SEASONALITY CHALLENGES AND FINANCIAL STABILITY IN UZBEKISTAN’S MINERAL ENTERPRISES - Alisher Akramovich Kilichev (International Journal of Economic Integration and Regional Competitiveness, 2024)
Background: The reliance on mineral resources is crucial for the economic vitality of regions like Deposit, Uzbekistan; however, the seasonality of resource availability poses significant challenges. Specific Background: This study focuses on how fluctuating access to mineral resources impacts the financial and operational stability of local enterprises, particularly during off-peak seasons. Knowledge Gap: Despite the importance of understanding these dynamics, there is a lack of literature addressing context-specific strategies for mitigating seasonal impacts on resource-dependent enterprises in Uzbekistan. Aims: This research aims to identify and analyze the financial and operational challenges faced by enterprises in Deposit, as well as the strategies they employ to cope with these seasonal disruptions. Results: Through qualitative analysis of semi-structured interviews with 110 participants, including enterprise managers, workers, and policymakers, the study finds that decreased resource availability and erratic cash flow are primary concerns. Many enterprises resort to short-term cost-cutting measures, which, while providing immediate financial relief, threaten long-term operational efficiency and workforce retention. Novelty: This study uniquely contributes to the literature by highlighting the specific challenges faced in Deposit and examining the effectiveness of current coping strategies in a resource-dependent economy. Implications: The findings suggest that targeted government interventions, such as tax incentives during off-peak seasons and improvements in infrastructure, are essential for alleviating these challenges. Additionally, promoting diversification into complementary industries could enhance year-round financial stability. This research lays the groundwork for future studies on implementing these strategies and exploring alternative financial approaches in similar economies.